Enhancement of the Quality of Onion Drying Using Tray Dryer - Fadilah, Siska Nuri; Khamil, Achri Isnan; Muharja, Maktum; Darmayanti, Rizki Fitria; Aswie, Viqhi (CHEESA: Chemical Engineering Research Articles, 2022)
Previous reports showed that there has been a continuous increase in the annual production of onion in Indonesia, and it is inversely proportional to the market price. The price drop is often caused by the high water content, which makes it easy to rot. Preservation of onions through a tray dryer is a good preservation method because it is effective and does not require much energy. Therefore, this study aims to determine the effect of variations in time, material thickness, and air velocity on the drying rate of onions. The samples were sliced to a size of 2 - 5 mm, followed by drying for 60 min using a tray dryer with different air rates between 4 - 7 m/s, and the rate of the process was observed every 15 min. The results showed that the drying time reduced the humidity in the chamber. The highest rate of 0.525 g/min was obtained at the peak air rate of 7 m/s. ANOVA results revealed that variations in time, onion thickness, and flow rate have a significant effect on increasing the drying rate of onions. This indicates that the method can be an effective and efficient solution to optimize the drying of the commodity.